EMU enlargement, stabilization costs and insurance mechanisms - Afonso, António (2022)
This paper considers the determinants of the macroeconomic costs of joining EMU for the new EU Member Sates, and compares them with those of the EMU members. Specifically, we investigate the business cycle correlation between the candidate’s economy and that of the euro area as a whole, and the ability of insurance mechanisms and fiscal policies to smooth income fluctuations. The results suggest that EMU membership would not be costly for some countries (Cyprus, Hungary and Malta) but for other countries it could have relevant costs, at least in the short-run. For some of these countries, business cycles are not yet well synchronized with the euro area’s business cycle, and risk-sharing mechanisms do not provide enough insurance against shocks.